Enhanced stability of Ni monosilicide on MOSFETs poly-Si gate stack - Mangelinck, D. (2013)
The formation and stability of Ni(Pt)Si on metal oxide semiconductor field effect transistor (MOSFETs) polycrystalline-Si (poly-Si) gate stack was investigated. Poly-Si and partial amorphous Si (a-Si) structures were grown using LPCVD and RTCVD techniques. For pure Ni silicidation, nucleation of NiSi2 was found at 700°C, which is slightly lower than that on monocrystalline Si (about 750°C). With Pt addition, Ni(Pt)Si was found up to 800°C, implying the important role of Gibbs free energy changes in enhancing the monosilicide stability. The extent of layer inversion of Ni(Pt)Si on RTCVD-Si is less than that on LPCVD-Si and thus results in a slower sheet resistance degradation.